Credibilidade de exemplos em classificação automática - Joao Rafael de Moura Palotti (2011)
Organization and recovery of large amounts of information became tasks of extreme importance, especially on the areas of Data Mining and Information Recovery, which are responsible for finding a way to deal with this data explosion. Among the topics studied in these two areas, there is the Automatic Classification of data.In this thesis, we treat the problem of automatically classifying the available information. In particular, this work was developed on the consideration that not all examples in a training set contribute equally to the construction of a classification model, so, assuming that some examples are more trustworthy than others can increase the effectiveness of the classifier. To deal with this problem, we propose the use of credibility functions capable of capturing how much a classifier should trust an example while generating the model.Credibility in the literature is considered as context dependent and also dependent on who is estimating it. To make its evaluation more objective, it is recommended that the factors used for its calculation are defined. We defined that, from the classifier's view, there are two crucial factors: the attribute/class relations and relationships among examples. The attribute/class relation can be easily extracted using lots of metrics already proposed in the literature, especially for the task of selecting the attributes. The relationships among the examples can be deduced from a feature that appear in the database. For example, in the context of document classification, it is shown that the networks of citations and authorship (which relate two documents based on its authors or citations) are a big source of information for the classification. Several metrics of complex networks can be used to quantify these relationships.Given these two factors, we selected 30 and 16 metrics to explore the attributes' and relationships' credibility respectively. They were inspired in metrics that occur in the literature, and indicate the separation among the classes and investigate characteristics of the relationship between the examples. Nevertheless, it is hard to tell which of these metrics is more appropriate to estimate the credibility of an example. So, since there is a big number of metrics for each factor, after some experiments with isolated metrics, we developed a Genetic Programming algorithm to better explore this search space, generating credibility functions capable of improving the effectiveness of classifiers associated with it.Genetic programming is an algorithm based on Darwin's theory of evolution, capable of traversing the search space of functions in a robust and effective way. The evolved functions were then incorporated to two classification algorithms: Naive Bayes and KNN. Experiments have been run using three different kinds of databases: document databases, UCI databases of categorical attributes and a protein signature database. The results show considerable improvement of the classification in all cases. In particular, for the database Oshmed, MacroF1 was improved by 17.51%, and for the protein signature database, Micro$F_1$ and Macro$F_1$ were improved by 26.58% and 50.78% respectively.